Roughness-based monitoring of transparency and conductivity in boron-doped ZnO thin films prepared by spray pyrolysis - Gaikwad, Rajendra S.; Bhande, Sambhaji S.; Mane, Rajaram S.; Pawar, Bhagwat N.; Gaikwad, Sanjay L.; Han, Sung-Hwan; Joo, Oh-Shim (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Sprayed polycrystalline ZnO and boron-doped ZnO thin films composed of spherical grains of 25-32 nm in diameters are used in roughness measurement and further correlated with the transparency and the conductivity characteristics. The surface roughness is increased up to Zn0.98B0.02O and then declined at higher boron concentrations. The sprayed ZnO films revealed >= 95% transmittance in the visible wavelength range, 1.956 x 10(-4) Omega cm electrical resistivity, 46 cm(2)/V s Hall mobility and 9.21 x 10(21) cm(-3) charge carrier concentration. The X-ray photoelectron spectroscopy study has confirmed 0.15 eV binding energy change for Zn 2p(3/2) when 2 at% boron content is mixed without altering electro-optical properties substantially. Finally, using soft modeling importance of these textured ZnO over non-textured films for enhancing the solar cells performance is explored. (C) 2012 Elsevier Ltd. All rights reserved.